CREEP DAMAGE CONSTITUTIVE MODEL OF FE-CR-NI BASED AUSTENITIC STAINLESS STEEL - GUO XiaoFeng; LIU BenXin; NAN NingNing; GONG JianMing; DONG ZhiMing (Jixie qiangdu, 2022)
Considering the effect of carbide coarsening and void nucleation and growth on the creep damage of Fe-Cr-Ni based austenitic stainless steel, a new creep damage constitutive model was established based on the hyperbolic sinh function, and material parameter optimization procedure of the model was also developed. In addition, a comparative assessment of extrapolated failure times for 3 creep damage models was undertaken for the standard uniaxial round-bar specimen using finite element software.The results show that the proposed constitutive model is capable to reflect the creep behavior of the material under different stress levels at 890 ℃. Compared with the failure time predicted by the widely used power law model（Kachanov-Robotnov model and Liu-Murakami model）, the prediction results of the current model can reflect the nonlinear relationship between stress and creep rupture time under double logarithmic coordinates in a wide stress range, so the prediction results are more reasonable.